Engaging Client’s Family and Friends in Online Counseling - Alemi, Farrokh (2005)
This paper describes how online counseling can be used to engage family members in the recovery of clients. The counselor guides the client and the family member separately through the stages of change, helping them commit to joint action. Each participant thinks through his/her concerns and the advantages of getting involved, each makes a specific commitment to working together under the guidance of the counselor. Finally each celebrates, with specific rituals, their decision to work together. Once the client and the family members commit to working together, the counselor guides them through the stages of change as a group. In the pre-contemplation stage, the family members are taught the goals of working together and the procedures to avoid dysfunctional conflict. In the contemplation phase, the client and the family members examine the shared environment and its links to target behavior. In the commitment to action stage, the client and the family members decide on specific changes in their shared environment. In the maintenance phase, the client and the family members analyze if the change has led to improvements. They analyze relapses and make additional cycles of improvement.